Quad-ridge horn antenna with elliptically shaped sidewalls for use as a reflector feed for radio astronomy - Odendaal, J.W. (Johann Wilhelm) (University of Pretoria, 2013)
Dissertation (MEng)--University of Pretoria, 2012.